Orthotopic model for the analysis of melanoma circulating tumor cells - Pícková, Markéta; Kahounová, Zuzana; Radaszkiewicz, Tomasz; Procházková, Jiřina; Fedr, Radek; Nosková, Michaela; Radaszkiewicz, Katarzyna Anna; Ovesná, Petra; Bryja, Vítězslav; Souček, Karel (Scientific reports, 2024)
Metastatic melanoma, a highly lethal form of skin cancer, presents significant clinical challenges due to limited therapeutic options and high metastatic capacity. Recent studies have demonstrated that cancer dissemination can occur earlier, before the diagnosis of the primary tumor. The progress in understanding the kinetics of cancer dissemination is limited by the lack of animal models that accurately mimic disease progression. We have established a xenograft model of human melanoma that spontaneously metastasizes to lymph nodes and lungs. This model allows precise monitoring of melanoma progression and is suitable for the quantitative and qualitative analysis of circulating tumor cells (CTCs). We have validated a flow cytometry-based protocol for CTCs enumeration and isolation. We could demonstrate that (i) CTCs were detectable in the bloodstream from the fourth week after tumor initiation, coinciding with the lymph node metastases appearance, (ii) excision of the primary tumor accelerated the formation of metastases in lymph nodes and lungs as early as one-week post-surgery, accompanied by the increased numbers of CTCs, and (iii) CTCs change their surface protein signature. In summary, we present a model of human melanoma that can be effectively utilized for future drug efficacy studies.
Keywords: Skin Neoplasms; Neoplastic Cells, Circulating; Circulating tumor cells; Melanoma; Lymphatic Metastasis; Tumorectomy; nádory kůže; lymfatické metastázy; průtoková cytometrie; Animals; lidé; nádorové cirkulující buňky; melanom; Metastasis; Humans; zvířata; Flow Cytometry; In vivo model